THE IMPACT OF COMMUNICATIVE COMPETENCE ON FOREIGN LANGUAGE SKILLS (American Journal of Pedagogical and Educational Research, 2023)
A competency-based approach to teaching a foreign language, according to the author, is one technique to boost students' enthusiasm to learn the language, enhance activity and creativity, and strengthen their learning activities. The best practices for teaching foreign languages to students are outlined in this article, with a focus on competency-based learning.